1976
DOI: 10.2337/diab.25.11.1055
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Carbohydrate Metabolism in Amyotrophic Lateral Sclerosis and Parkinsonism-dementia on Guam

Abstract: Amyotrophic lateral sclerosis and Parkinsonism-dementia are unusually prevalent on Guam. Carbohydrate metabolism was studied in 110 patients with evidence diagnostic of or suspecious for these diseases. The combined incidence of known diabetes in 29 per cent of them plus a high percentage of glucose tolerance tests interpreted as abnormal, even when most age-related criteria were considered, was considerably higher than the incidence of abnormal carbohydrate metabolism reported elsewhere in the general populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…However, the incidence of abnormal glucose tolerance tests in ALS patients ranges from 19-72% [9,113,115,116,117,118], and therefore subtle alterations in glucose handling could occur in ALS. Abnormal glucose metabolism does not appear to affect survival or disease severity [114,119]; however, one Taiwanese study reported an increased risk of ALS in those with DM [120].…”
Section: Meeting Energy Needs In Alsmentioning
confidence: 99%
“…However, the incidence of abnormal glucose tolerance tests in ALS patients ranges from 19-72% [9,113,115,116,117,118], and therefore subtle alterations in glucose handling could occur in ALS. Abnormal glucose metabolism does not appear to affect survival or disease severity [114,119]; however, one Taiwanese study reported an increased risk of ALS in those with DM [120].…”
Section: Meeting Energy Needs In Alsmentioning
confidence: 99%
“…The overall study size varies from 18 to 2371 participants with ALS. Diagnosis of ALS was based on EL Escorial criteria in 3 studies [7-9], on clinical criteria only in one study [10], on the combination of clinical and electromyographic (EMG) criteria in one study [11]; and it was not reported in two studies [12,13]. Likewise the diagnosis of diabetes mellitus and impaired glucose tolerance varies across studies.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise the diagnosis of diabetes mellitus and impaired glucose tolerance varies across studies. Two studies used the WHO 1997 criteria [8,9], one study use the United states public health service and the national diabetes data group criteria [12], while diagnosis criteria for diabetes mellitus and dysglycemia were not provided in 3 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of seven, predominantly retrospective, observational studies found no increase in the prevalence of diabetes mellitus (DM) in ALS (Lekoubou et al, 2014), although the incidence of abnormal glucose tolerance tests in ALS patients ranges from 19% to 72% (Ionasescu and Luca, 1964, Mueller and Quick, 1970, Koerner, 1976, Harno et al, 1984, Armon et al, 1991, Pradat et al, 2010. Therefore subtle alterations in glucose handling could occur in ALS.…”
Section: Impaired Glucose Handlingmentioning
confidence: 99%